1986
DOI: 10.1177/027614678600600105
|View full text |Cite
|
Sign up to set email alerts
|

Marketing and Economic Development: Review, Synthesis and Evaluation

Abstract: The authors present a review, synthesis and evaluation of the published works on marketing and economic development o ver the last 30 years. Future research directions are also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The lack of managerial know-how, inefficient distribution systems, low trade margins and large number of small suppliers were cited as evidence for the nonexistence of (western) marketing in the Third World (Drucker, 1958; Kaynak and Hudanah, 1987). Further, researchers reported that, in less developed countries, marketing was mostly seen as a ‘parasitic’ activity (Kaynak and Hudanah, 1987; Van Wood and Vitell, 1986).…”
Section: Third World and Difference In Absencementioning
confidence: 99%
“…The lack of managerial know-how, inefficient distribution systems, low trade margins and large number of small suppliers were cited as evidence for the nonexistence of (western) marketing in the Third World (Drucker, 1958; Kaynak and Hudanah, 1987). Further, researchers reported that, in less developed countries, marketing was mostly seen as a ‘parasitic’ activity (Kaynak and Hudanah, 1987; Van Wood and Vitell, 1986).…”
Section: Third World and Difference In Absencementioning
confidence: 99%
“…Generally this type of research aims to produce managerially useful insights that aim to predict consumer behaviour in order to better control it (e.g. Wood & Vitell, 1986). As Arndt (1985, p. 16) explains, this paradigm conceptualises the social world as 'essentially…harmonious and conflict free'.…”
Section: An Example Of a Sequential Multiple Paradigm Reviewmentioning
confidence: 99%
“…This means such research generally aims to explain the social world as it is, assuming that the status quo (i.e. the continuing economic development of the planet and the growth of consumerism) is comparatively unproblematic (see Wood & Vitell, 1986). Given its belief in objectivity and methodological commitments to lab experiments, questionnaires and large-scale surveys (Wansink, 2012), research based on this paradigm draws from the existing literature to develop hypotheses that are subsequently tested against the empirical world and falsified or verified, with the intention of producing generalisable theory which can inform the roll-out of marketing practice throughout the world (Wood & Vitell, 1986).…”
Section: An Example Of a Sequential Multiple Paradigm Reviewmentioning
confidence: 99%
See 1 more Smart Citation